2017
DOI: 10.29252/ijree.2.4.31
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-Based Contrastive Analysis of Stance Strategies in Native and Nonnative Speakers’ English Academic Writings: Introduction and Discussion Sections in Focus

Abstract: The present study was an attempt to illustrate the interaction between writers and readers. Conveying of the writers' voice, stance, and interaction with reader was put forward within this paradigm. Being a good academic writer is highly related to the use of these strategies. Adopting a position and persuading readers of claims are very important. This study was aimed at showing the differences between Iranian and American M.A. EFL writers in using stance strategies (hedges, boosters, attitude markers, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…The results of this study partly support Shirzadi et al (2017)'s study who conducted a corpusbased contrastive analysis of stance strategies in native and nonnative speakers' English academic writings. That is, the findings of the present research also indicated that nonnative writers made more use of boosters than native writers in their academic papers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of this study partly support Shirzadi et al (2017)'s study who conducted a corpusbased contrastive analysis of stance strategies in native and nonnative speakers' English academic writings. That is, the findings of the present research also indicated that nonnative writers made more use of boosters than native writers in their academic papers.…”
Section: Discussionsupporting
confidence: 80%
“…Several research have been conducted on hedges and boosters in the related literature (Akbas, 2012(Akbas, , 2014Can & Yuvayapan, 2018;Chen, 2012;Coates, 1987;Holmes, 1990;Holtgraves & Lasky, 1999;Kim & Suh, 2014;Shirzadi, Akhgar, Rooholamin, & Shafiee, 2017;Vassileva, 2001;Yağız & Demir, 2015). For instance, Vassileva (2001) conducted a crosslinguistic and comparative study regarding commitment and detachment in English and Bulgarian academic texts.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Shirzadi et al, (2017) also investigated the differences between Iranian and American M.A. EFL writers in using stance strategies (hedges, boosters, attitude markers, and self-mentions) in Introduction and Discussion sections of academic papers.…”
Section: Previous Studies On Metadiscourse Analysismentioning
confidence: 99%
“…Tasks are challenging and interesting and engage learners in the learning process. Tasks have been extensively used throughout the EFL/ESL researches as effective tools to evoke language development, engagement, meaning negotiation, input processing, and form focus, all of which are thought to improve foreign language learning (Nunan, 2004;Shirzadi, Akhgar, Rooholamin, & Shafiee, 2017). Prabhu (1987) defines a task as "an activity that requires learners to arrive at an outcome from given information through some process of thought, and which allows teachers to monitor and regulate that process" (p. 134).…”
Section: Theoretical or Conceptual Frameworkmentioning
confidence: 99%